The Implementation Of The Functions Of The Village Council (BPD) In The Administration Of Village Governance In Situterate Village - Heru Wahyudi (Jurnal Scientia, 2024)
This study aims to analyze the implementation of the functions of the Village Council (BPD) in the administration of village governance in Situterate Village, Cikande District, Serang Regency. The research method used is qualitative with a descriptive approach, involving in-depth interviews, observations, and document studies. The findings indicate that the understanding of BPD members regarding their duties and functions is still limited, particularly in the areas of legislation and supervision. The level of education and training of BPD members significantly affects the effectiveness of their task performance, with better-educated and trained members demonstrating greater competence in fulfilling their roles. Coordination between BPD and the village government also needs improvement, especially in communication and role clarity. Moreover, public participation in village governance remains low, primarily due to a lack of socialization and transparency in the decision-making process. Bureaucratic complexity and administrative hurdles frequently impede the implementation of BPD work programs. The study suggests enhancing training, education, and coordination, as well as simplifying bureaucracy to support more effective BPD task execution.